(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The higher education sector is in the midst of fundamental change. Never before has there been such intense public debate about the place of the university and its role in society. During the 1980s and 1990 there was significant growth in the number of student studying part–time and through distance learning. The single most dramatic effect of paradigm shift is learner sovereignty. The teacher role at least as defined by the instructvists now belongs to a bygone era. Students have much greater autonomy over their learning, in terms of when, where and how they learn. Interaction with fellow students and faculty are literally (and metaphorically) at their fingertips. In this review paper an asynchronous discussion boards as the modus operandi, learner interaction is heightened.